THE STUDY OF MENTAL STATES TENNIS PLAYERS OF VARYING QUALIFICATIONS DURING THE COMPETITION - Tsagelnikova , A. A.; Boyarina , Yu. S.; Tsiganov , O. V. (Modern Psychology, 2019)
In this article we examined the mental States tennis players of different skills in the process of competitive activity. Presents the results of psychological testing and the results of pedagogical observation of external signs of competitive tennis before the emotional state of 14 years of various sports skills.